Hereditary optic neuropathy associated with demyelinating diseases of the central nervous system - Eliseeva, D D; Kalashnikova, A K; Bryukhov, V V; Andreeva, N A; Zhorzholadze, N V; Murakhovskaya, Yu K; Krilova, T D; Tsygankova, P G; Zakharova, M N; Sheremet, N L (Zhurnal nevrologii i psikhiatrii imeni S.S. Korsakova, 2023)
Demyelinating optic neuritis and hereditary optic neuropathy (HON) take a leading place among the diseases, the leading clinical syndrome of which is bilateral optic neuropathy with a simultaneous or sequential significant decrease in visual acuity. Optic neuritis can occur at the onset or be one of the syndromes within multiple sclerosis (MS), neuromyelitis optica spectrum disorders (NMOSD), and myelin oligodendrocyte glycoprotein (MOG) antibody disease (MOGAD). HON are a group of neurodegenerative diseases, among which the most common variants are Leber's hereditary optic neuropathy (LHON), associated with mitochondrial DNA (mtDNA) mutations, and autosomal recessive optic neuropathy (ARON), caused by nuclear DNA (nDNA) mutations in . There are phenotypes of LHON «plus», one of which is the association of HON and CNS demyelination in the same patient. In such cases, the diagnosis of each of these diseases causes significant difficulties, due to the fact that in some cases there are clinical and radiological coincidences between demyelinating and hereditary mitochondrial diseases.